Invasion, metastasis and stem cells - Weinberg, Robert (Henry Stewart Talks, 2009)
Vogelstein-Kinzler model of multi-step colon cancer pathogenesis, Cell of origin determines tumor morphology and behaviour, Hierarchical organization of normal epithelial tissues, Similar hierarchical organization of cancer cells in a tumor, The invasion-metastasis cascade, Physical dissemination, Adaptation to and proliferation in a foreign tissue, Colonization, Epithelial-mesenchymal transition (EMT), The microenvironment of the primary tumor, Twist transcription factor, Slug TF, What is the nature of cells generated by an EMT?, EMT and cancer progression